Cultivar-Dependent Responses in Plant Growth, Leaf Physiology, Phosphorus Use Efficiency, and Tuber Quality of Potatoes Under Limited Phosphorus Availability Conditions - Chea, Leangsrun; Meijide, Ana; Meinen, Catharina; Pawelzik, Elke; Naumann, Marcel (Frontiers in Plant Science, 2021)
Limited availability of phosphorus (P) in soils causes a major constraint in the productivity of potato, which requires increased knowledge on plant adaptation responses under this condition. In the present study, six potato cultivars—Agria, Lady Claire, Milva, Lilly, Sieglinde, and Verdi—were assessed for their responses on plant growth, leaf physiology, P use efficiency, and tuber quality under three P levels (Plow, Pmed, and Phigh). The results reveal a significant variation of cultivars in response to different P availabilities. P-efficient cultivars—Agria, Milva, and Lilly—possessed substantial plant biomass, tuber yield, and high P uptake efficiency under low P supply. The P-inefficient cultivars—Lady Claire, Sieglinde, and Verdi—lacked the ability to produce tubers under P deprivation, as well as the ability for efficient P uptake under low P level, but they were efficient in P uptake under high soil P. Improved P uptake efficiency is important for plant tolerance under limited P availability, which results in efficient use of the applied P. At the leaf level, increased accumulations of nitrate, sulfate, sucrose, and proline are necessary for a plant to acclimate to P deficiency-induced stress and to mobilize leaf inorganic phosphate to increase internal P use efficiency and photosynthesis. The reduction of plant biomass and tuber yield under P deficiency could be caused by the reduced CO2 assimilation. Furthermore, P deficiency significantly reduced tuber yield, dry matter, and starch concentration in Agria, Milva, and Lilly. Nevertheless, contents of tuber protein, sugars, and minerals, as well as antioxidant capacity were enhanced under this condition in these cultivars. These results highlight the important traits contributing to potato plant tolerance under P deficiency and indicate an opportunity to improve P efficiency and tuber quality of potato under the deficient conditions by using more efficient cultivars. Future research on evaluating molecular mechanisms related to P and sucrose translocation, as well as minimizing tuber yield reduction under limited P availability is necessary.